Willingness to Pay for Maternity Waiting Homes in Rural Indonesia - Arlina Dewi; Supriyatiningsih Supriyatiningsih; Sri Sundari; Dianita Sugiyo; Ralph. J. Lellee (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2020)
Distance to a health care facility has long been discussed as a key barrier to maternal health care utilization in rural areas. Maternity Waiting Homes (MWHs) has been proved to the reductions of maternal mortality. The objective of this study was to investigate the pregnant women’s Willingness to Pay (WTP) toward the maternity waiting homes (MWHs). The cross-sectional study was conducted in two rural areas in South Sulawesi, Indonesia. The data were collected through survey which was distributed to pregnant women and their families. A total of fifty-one pregnant women and forty-nine families participated in the study as two groups of respondents. For the results of this study, there were 66.7% of pregnant women agreed if they should stay at MWHs. For a group of pregnant women, the amount of WTP which was capable to be paid was 100.000 IDR in a month. Moreover, for a group of family, the amount of WTP which they could pay for staying at MWH was 200.000 IDR in a month. The pregnant women’s acceptance to stay in MWH is good, but their willingness to pay is still very low.